Peningkatan Efisiensi Peternakan Unggas melalui Mesin Penetas Telur Otomatis: Program Pemberdayaan bagi Warga Binaan di Lembaga Pemasyarakatan Kelas I Malang - Chefin Satya Syaffatullah; Soma Hadi Shibyana; Muhammad Ali Rhojab; Firmanda Bernard Satriya; Muhammad Nuril Mubin; Ayu Windiasari; Tri Wahyu Hardaningrum (jurnal ABDIMAS Indonesia, 2025)
This community service program at the Class I Correctional Facility SAE L’SIMA Malang was designed to address the urgent need for effective vocational skills development among inmates through productive poultry farming activities. One of the key challenges in poultry farming is the low success rate of egg hatching when relying on conventional, manually operated incubators that often lack precise temperature and humidity control. To overcome this problem, the program introduced the development and implementation of an automatic incubator system as a technological innovation to support both learning and productivity. The program employed a participatory approach, beginning with preliminary site surveys to identify existing resources and limitations within the correctional facility. Subsequently, the team carried out the design and assembly of an automatic egg incubator equipped with a digital system to monitor and regulate temperature and humidity levels. Functional testing was conducted using both chicken and duck eggs to ensure reliability and applicability across different types of poultry. In addition to the incubator prototype, the program also produced a practical user manual to guide inmates in operating and maintaining the equipment independently. The results demonstrated that the automatic incubator significantly improved the hatching success rate compared to traditional manual methods, despite initial challenges such as limited availability of components, restricted funding, and the reliance on outdated manual equipment. The inmates showed high levels of participation and adaptability in learning the operation of the new system, highlighting the potential of this program to enhance not only technical competence but also self-confidence. In conclusion, this initiative successfully integrated vocational training with technological innovation, offering a sustainable and practical solution for small to medium-scale poultry operations. Beyond improving technical skills, the program has broader social implications by equipping inmates with marketable competencies that can support their reintegration into society and contribute to their economic independence after release.